Simultaneous determination of kolliphor HS15 and miglyol 812 in microemulsion formulation by ultra-high performance liquid chromatography coupled with nano quantity analyte detector - Honggen Zhang; Zhenyu Wang; Oscar Liu (Elsevier, 2016)
A novel method for simultaneous determination of kolliphor HS15 and miglyol 812 in microemulsion formulation was developed using ultra-high performance liquid chromatography coupled with a nano quantitation analytical detector (UHPLC-NQAD). All components in kolliphor HS15 and miglyol 812 were well separated on an Acquity BEH C18 column. Mobile phase A was 0.1% trifluoroacetic acid (TFA) in water and mobile phase B was acetonitrile. A gradient elution sequence was programed initially with 60% organic solvent, slowly increased to 100% within 8 min. The flow rate was 0.7 mL/min. Good linearity (r>0.95) was obtained in the range of 27.6-1381.1 μg/mL for polyoxyl 15 hydroxystearate in kolliphor HS15, 0.8-202.0 μg/mL for caprylic acid triglyceride and 2.7-221.9 μg/mL for capric acid triglyceride in miglyol 812. The relative standard deviations (RSD) ranged from 0.6% to 1.7% for intra-day precision and from 0.4% to 2.7% for inter-day precision. The overall recoveries (accuracy) were 99.7%-101.4% for polyoxyl 15 hydroxystearate in kolliphor HS15, 96.7%-99.6% for caprylic acid triglyceride, and 94.1%-103.3% for capric acid triglyceride in miglyol 812. Quantification limits (QL) were determined as 27.6 μg/mL for polyoxyl 15 hydroxystearate in kolliphor HS15, 0.8 μg/mL for caprylic acid triglyceride, and 2.7 μg/mL for capric acid triglyceride in miglyol 812. No interferences were observed in the retention time ranges of kolliphor HS15 and miglyol 812. The method was validated in terms of specificity, linearity, precision, accuracy, QL, and robustness. The proposed method has been applied to microemulsion formulation analyses with good recoveries (82.2%-103.4%).